TRADITIONAL DOWRY IN REPRESSING PAPUAN WOMEN’S POLITICAL REPRESENTATION JAYAPURA CITY LEGISLATIVE 2014-2019 - Snanfi, Ferinandus Leonardo (JWP (Jurnal Wacana Politik), 2024)
This research investigated the impact of traditional dowry payments on the low political representation of indigenous Papuan women in the Jayapura City legislature from 2014 to 2019. Despite the election of four indigenous Papuan women to the Jayapura City legislature in 2014, there remains a significant gap in representation. This qualitative research gathered data through interviews with 30 respondents, including seven influential community figures, seven husbands of indigenous Papuan women, six Papuan students, two lecturers, three members of political parties, two female Papuan legislators, one representative from the General Election Commission, one member of the Papuan People’s Council, and the head of the Population and Civil Registry Service. Observational data were gathered from the General Election Commission Office and the indigenous Papuan community in Jayapura City. Documentation review further supplemented the research, focusing on legislative representation data, voter turnout, and customary dowry payment records for indigenous Papuan women. The data underwent rigorous re-validation to ensure the analysis accurately reflected the reality of how traditional dowry practices hinder the political participation of indigenous Papuan women in the Jayapura City legislature during the specified period. The findings reveal that the obligation for indigenous Papuan women to adhere to their husbands’ directives, a consequence of dowry payments, significantly limits their ability to engage in political activities, including legislative candidacy and community campaigning. This restriction was exemplified in the 2019 election, where only one indigenous Papuan woman was elected to the Jayapura City legislature.